Trends in Threat Status and Priorities in Conservation of the Woodpeckers of the World - Lammertink, J. Martjan (2014)
Taking the first IUCN Red List from 1988 as a starting point, I review trends in the threat status of the woodpecker species of the world, the geographical distribution of (near-) threatened woodpecker species, threat factors affecting these species, and the research output about them. Between 1988 and 2013 the number of genuinely Red Listed woodpeckers (categories Near Threatened and up) increased from 20 to 28 species and the number of species in the categories Vulnerable and up from 8 to 12. As percentage of recognised woodpecker species in the different years, the increase in Red Listed woodpecker species was even sharper. The geographical distribution of Red Listed woodpeckers stayed constant between 1988 and 2013, with over half of the species in Latin America, about one quarter in Asia, and none in Europe. A taxonomic reappraisal adopted by IUCN in 2014 raised the total number of recognised woodpecker species to 254 and of Red Listed woodpecker species to 42, of which 40% occur in Asia. Nearly all Red Listed woodpecker species on the 2013 list are threatened by deforestation. Out of 28 species, 10 are also threatened by selective logging, and these 10 are in higher threat categories. Woodpecker conservation research should focus in particular on the species sensitive to selective logging, to assess their within-habitat requirements and thresholds. The output of research on Red Listed woodpeckers in the past 25 years was heavily skewed to three North American species: Red-headed Woodpecker Melanerpes erythrocephalus, Red-cockaded Woodpecker Picoides borealis and Ivory-billed Woodpecker Campephilus principalis. I identify 10 priority species to focus woodpecker conservation research on, four from Latin America: Speckle-chested Piculet Picumnus steindachneri, Fernandina's Flicker Colaptes fernandinae, Black-bodied Woodpecker Dryocopus schulzi, Helmeted Woodpecker Dryocopus galeatus; and six from Asia: Okinawa Woodpecker Dendrocopos noguchii, Korean White-bellied Woodpecker Dryocopus richardsi, Great Slaty Woodpecker Mulleripicus pulverulentus, Red-collared Woodpecker Picus rabieri, Yellow-faced Flameback Chrysocolaptes xanthocephalus and Whiterumped Woodpecker Meiglyptes tristis